The Mandative be and were Subjunctives in Online British and American Corpora: A Contrastive Study (Journal of the College of Basic Education, 2025)
This study examines the differences between British English and American English in the preference for should or the possibility of indicative forms in British English versus the overwhelming preference for be-subjunctives in American English is confirmed by the present- day data. The Mandative subjunctive is used to express suggestion, wishes, and demands and its usage has become subject to variation across various English dialects. The research uses data from the British National Corpus (BNC) on one hand, and from the Corpus of Contemporary American English (COCA) on the other, searching for contexts with similar triggers, like "requested that," "demanded that," and "urged that." The findings show that there is still an obvious preference for should in British English and for synthetic forms in American English, even though this paper also reveals there is a significant number of synthetic forms in the British English which contradict the traditional view that differentiates the two varieties. In contrast, the use of be-subjunctive is still strongly favored in American English. The results partially support statements regarding the distinctions between British and American English in terms of the mandative subjunctives.